Perception and Challenges among Medical Faculty in Implementation of Competency-Based Medical Education (CBME): A Qualitative Study - Ginni Agrawal; Satpinder Jit Mohan; Piyush Jain; Ruchi Sharma (Universitas Airlangga, 2026)
Medical education in India is undergoing a transition with the introduction of Competency-Based Medical Education (CBME) by the National Medical Commission. CBME represents a shift toward outcome-oriented, learner-centered training that aims to produce competent Indian Medical Graduates (IMGs) through structured competencies, formative assessment, and continuous feedback. Despite its potential benefits, implementation across medical institutions has encountered several challenges. To explore medical faculty perceptions regarding CBME and to identify key challenges encountered during its implementation. A qualitative study was conducted over two months (June–July 2024) among first-phase faculty members involved in implementing the CBME curriculum at a medical college. In-depth interviews were conducted with 12 faculty members after obtaining informed consent. Data were analyzed using thematic analysis of open-ended interviews. Faculty perceived CBME as a positive reform that enhances skill development, encourages learner-centered teaching, and improves students' early clinical exposure and clinical preparedness. However, significant challenges were identified, including inadequate faculty strength, insufficient training, limited infrastructure and logistical support, time constraints due to fixed schedules, and a lack of uniformity in assessment and implementation across institutions. Although faculty perceptions toward CBME were largely positive, its successful implementation requires focused faculty development, adequate human and infrastructural resources, structured student orientation, and standardized implementation strategies across medical colleges.